2011
DOI: 10.1080/11250003.2011.564214
|View full text |Cite
|
Sign up to set email alerts
|

Male age influence on male reproductive success inDrosophila ananassae(Diptera: Drosophilidae)

Abstract: Male age influence on male mating success, courtship, mating activities, fecundity, fertility, longevity, percentage of egg-larval hatchability and percentage of larva-adult viability has been studied in Drosophila ananassae. It was noticed that females of D. ananassae were able to discriminate males on the basis of male age and preferred to mate with old-aged males more frequently than younger or middle-aged males using a female choice experiment. Old-aged males significantly mated faster, performed greater c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In the present study on D. bipectinata , females who mated with old males received more protein and more sperm, allowing them to have a higher fecundity and produce more progeny than females who mated with young and middle-age males ( Tables 3 and 4 , Figure 5 ). This result could be why females of D. bipectinata prefer older males more than middle-age and young males, as was noticed in an earlier study on three different geographical strains ( Prathibha and Krishna, 2011 ; Somashekar and Krishna 2011 ). Although only one strain was used in our present study, because the female preference for old males was found in all the three geographical populations of D. bipectinata in other studies, the results of the present study in relation to accessory gland variation in young, middle, and old males and its effect on fecundity and fertility could also be extended to other strains.…”
Section: Discussionsupporting
confidence: 59%
“…In the present study on D. bipectinata , females who mated with old males received more protein and more sperm, allowing them to have a higher fecundity and produce more progeny than females who mated with young and middle-age males ( Tables 3 and 4 , Figure 5 ). This result could be why females of D. bipectinata prefer older males more than middle-age and young males, as was noticed in an earlier study on three different geographical strains ( Prathibha and Krishna, 2011 ; Somashekar and Krishna 2011 ). Although only one strain was used in our present study, because the female preference for old males was found in all the three geographical populations of D. bipectinata in other studies, the results of the present study in relation to accessory gland variation in young, middle, and old males and its effect on fecundity and fertility could also be extended to other strains.…”
Section: Discussionsupporting
confidence: 59%
“…We did, however, observe courtship behaviour (wing extension) in 60-day old males when paired with younger virgin females (data not quantified); consistent with this, so far no study has reported a cut-off age for male mating drive in Drosophilid flies. While individual parameters of male mating performance decline with age 32 ; other parameters appear to increase 33 , suggesting that the observed loss of response is not a loss of mating interest per se. Moreover, baseline locomotor activities of 60-day-old flies were the same as in 10-day-old flies (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…In support of this claim, some studies show that older males expend more effort when fighting for mates (e.g., Kemp 2006;Fischer et al 2008;Okada et al 2020). Likewise, older males are often more persistent during courtship (e.g., PĂ©rez-Staples et al 2010;Prathibha et al 2011;Karl and Fischer 2013;RodrĂ­guez-Muñoz et al 2019). Intriguingly, however, a new meta-analysis reported a nonsignif-icant trend for older males to invest less into sexual signaling (Dougherty 2021).…”
mentioning
confidence: 95%